2018
DOI: 10.11648/j.jwer.20180701.11
|View full text |Cite
|
Sign up to set email alerts
|

An Econometric Analysis of the Nexus of Exchange Rate, Inflation and Budget Deficit: Case of Nigeria 1981 – 2016

Abstract: Depreciation of the naira has a role to play in Nigeria's recent inflationary process. Concomitant with this is the substantial budget deficit operated annually by the Federal Government in the last decade or so. Part of the budget deficit is finance through bank credit which directly affects the money base. This also exerts upward pressure on the general price level. All this suggests that there are many sources of the current inflation. While the channels through which exchange rate depreciation affects pric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Suleiman Sa'ad et al (2018) evaluates the quantitative effects of exchange rate depreciation on budget deficit and inflation in Nigeria with SVAR, cointegration and the error correction model. The outcome shows trend in the affiliation between exchange rate, budget deficit and inflation and a positive impact on exchange rate, inflation and budget deficit but not statistically significant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Suleiman Sa'ad et al (2018) evaluates the quantitative effects of exchange rate depreciation on budget deficit and inflation in Nigeria with SVAR, cointegration and the error correction model. The outcome shows trend in the affiliation between exchange rate, budget deficit and inflation and a positive impact on exchange rate, inflation and budget deficit but not statistically significant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Suleiman, Alexander and Olure-Bank [41] assessed the quantitative impacts of budget shortfall and Naira exchange rate and how they impact price levels in Nigeria. The study used SVAR and found a zero impact of the public spending shortfall and the Naira exchange rate on the price level.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The performance of various macroeconomic indicators is now becoming greatly influences by the global economic factors (Kuchukova et al, 2016;Mishchenko et al, 2018;Molocwa, 2018;Suleiman Sa'ad & Michael, 2018). Globalization in recent times is significantly impacting the economic dynamics of all the countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Globalization is not new but its changing magnitude has profound implications that vary with economies depending upon their dynamics, structure and extent of openness (Taylor, 2006). More open economies have greater ability to capture new ideas (Obstfeld, 2004;Molocwa, 2018;Suleiman Sa'ad & Michael, 2018).…”
Section: Introductionmentioning
confidence: 99%